Do Long Bus Rides Drive Down Academic Outcomes?. (December 2022) - Cordes, Sarah A.; Rick, Christopher; Schwartz, Amy Ellen
School buses may be a critical education policy lever, breaking the link between schools and neighborhoods and facilitating access to school choice. Yet, little is known about the commute for bus riders, including the average length of the bus ride or whether long commutes harm academic outcomes. We begin to fill this gap using data from New York City to explore the morning commutes of more than 120, 000 bus riders. We find that long bus rides are uncommon and that those with long bus rides are disproportionately Black and more likely to attend charter or district choice schools. We find deleterious effects of long bus rides on attendance and chronic absenteeism of district choice students.